Local Community Distribution and Participation in Biodiversity Conservation in National Parks: A Case of Gashaka Gumti National Park Safety - Madaki, Kanati; Umaru, Isaac John; Umaru, Kerenhapucch Isaac (Darul Yasin Al Sys, 2024)
In this article, we investigate how the distribution of community participation impacts biodiversity conservation in national parks. This study analyzes factors that influence the distribution of community participation in biodiversity conservation. We hypothesize that employment in tourism increases the likelihood of community participation in biodiversity conservation. Additionally, we hypothesize that financial benefits derived by local people uniquely influence their likelihood of engaging in conservation activities. Furthermore, we hypothesize that infrastructure development affects household likelihood to engage in biodiversity conservation. Data were collected from households using questionnaires. Using logistic regression analysis, we find support for our hypotheses. The results suggest that local community participation in biodiversity conservation is significant. This study contributes to the growing empirical evidence on the effects of local community participation on biodiversity conservation in national parks and its implications for park managers and policymakers. Our study makes significant contributions to the existing literature and has practical implications for park management and policy formulation.